Impact of repetitive exposure to strong static magnetic fields on pregnancy and embryonic development of mice. Issue 3 (7th October 2013) - Zahedi, Yasmin; Zaun, Gregor; Maderwald, Stefan; Orzada, Stephan; Pütter, Carolin; Scherag, André; Winterhager, Elke; Ladd, Mark E.; Grümmer, Ruth
Abstract : Purpose: To evaluate possible risks of strong static magnetic fields for embryo implantation, gestation, organogenesis, and embryonic development. Materials and Methods: Pregnant mice were exposed for 75 minutes daily during the entire course of pregnancy at the bore entrance, representing the position of medical staff, and at the isocenter, representing the position of patients, of a 1.5 T and a 7 T human MRI scanner. Results: No effect of static magnetic field strength was observed with regard to pregnancy rate, duration of pregnancy, litter size, still births, malformations, sex distribution, or postpartum death of offspring. During the first 8 weeks postnatal, mice exposed in utero to a magnetic field strength of 1.5 T or stronger showed a slight delay in weight gain and in time to eye opening compared to controls. Conclusion: Daily exposure to strong magnetic fields during pregnancy had no deleterious effect on offspring; however, a developmental retardation could be observed postnatally with regard to weight gain and eye opening.J. Magn. Reson. Imaging 2014;39:691–699 . ©2013 Wiley Periodicals, Inc.